(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained the effective ways for integration of business ethics courses into the business education curriculum as a strategy for training students for improved performance in business organization, in the perception of business educators in tertiary institutions in South-East Nigeria. Descriptive survey research design was adopted for the study. The population of the study comprised 144 business educators in tertiary institutions in the South East, Nigeria. One research question guided the study and one hypothesis was tested at 0.05 level of significance. A nine item questionnaire was used for data collection. The questionnaire was tested for validity and the instrument determined for internal consistency using Cronbach alpha, which yielded a score of 0.74. The data collected were analysed using mean score, standard deviation and Analysis of Variance (ANOVA). The mean ratings were used to answer the research question while standard deviation was used to determine the closeness of the respondents’ means. Analysis of Variance was used in testing the null hypothesis at 0.05 level of significance. Findings revealed among others, providing foundational ethics courses in business education and discussing case studies in ethics in business education classes as effective ways of integration of business ethics courses in business education curriculum in tertiary institutions and a strategy for training students for improved performance in business organizations. Furthermore, the findings revealed that years of teaching experience of the respondents did not significantly influence their mean ratings on the effective ways of integration of business ethics courses in the business education curriculum, as a strategy for training students for improved performance in business organizations. It was recommended among others, that administrators of business education programme in tertiary institutions should apply the effective ways discovered in this study to integrate business ethics courses in business education curriculum for training of students and for improved performance of her graduates in business organisations. This will enable students to be theoretically and practically equipped for the labour market and the demands of the real world.